Representasi Perempuan dalam Film Tuhan Izinkan Aku Berdosa: Analisis Wacana Kritis Sara Mills - Agus Ainul Yaqin M.S; Ade Elsa Agustin; Wendra Ajistyatama (Social Science Academic, 2026)
Film as a cultural product does not merely function as entertainment but also serves as a site for the production and reproduction of discourses on gender, morality, religion, and power relations. This study aims to analyze the representation of women in the film Tuhan Izinkan Aku Berdosa using Critical Discourse Analysis from Sara Mills' perspective. The study employs a descriptive qualitative approach. Data in the form of scenes, dialogues, narratives, and visual elements featuring the character Kiran were collected through observation, documentation, and literature review. The analysis focuses on the subject-object position and the position of the reader or viewer. The findings indicate that Kiran is predominantly positioned as the object of narration, the object of moral judgment, and the object of violence. Male characters who possess social, academic, economic, and religious authority are afforded greater space to define reality and to evaluate Kiran. The study concludes that the film reveals a tension between women's resistance and the reproduction of patriarchal structures. Kiran's resistance is present, yet it is more often framed as an individual tragedy rather than a structural critique that fully empowers women.